The c.1460C>T Polymorphism of MAO-A Is Associated with the Risk of Depression in Postmenopausal Women - R. Słopień; A. Słopień; A. Różycka; A. Warenik-Szymankiewicz; M. Lianeri; P. P. Jagodziński (The Scientific World Journal)
Objective. The aim of the study was an evaluation of possible relationships between polymorphisms of serotoninergic system genes and the risk of depression in postmenopausal women. Methods. We studied 332 women admitted to our department because of climacteric symptoms. The study group included 113 women with a diagnosis of depressive disorder according to the Hamilton rating scale for depression; the controls consisted of 219 women without depression. Serum 17β-estradiol concentrations were evaluated using radioimmunoassay, while polymorphisms in serotoninergic system genes: serotonin receptors 2A (HTR2A), 1B (HTR1B), and 2C (HTR2C); tryptophan hydroxylase 1 (TPH1) and 2 (TPH2), and monoamine oxidase A (MAO-A) were evaluated using polymerase chain reaction-restriction. Results. We found that the 1460T allele of MAO-A c.1460C>T (SNP 1137070) appeared with a significantly higher frequency in depressed female patients than in the control group (P=0.011) and the combined c.1460CT + TT genotypes were associated with a higher risk of depression (P=0.0198). Patients with the 1460TT genotype had a significantly higher 17β-estradiol concentration than patients with the 1460CT genotype (P=0.0065) and 1460CC genotype (P=0.0018). Conclusions. We concluded that depression in postmenopausal women is closely related to the genetic contribution of MAO-A.